Future Hybrids in an Unsewn World - Mongili, Alessandro (Tecnoscienza – Italian Journal of Science & Technology Studies, 2020)
The contribution aims to outline the next steps of STS studies in order to challenge contingencies and changes in an unstable World. The crisis of One-World World’s approach and the appearance of multiplicity in different forms opened up the possibility to a more engaged STS. In this regard, a more lateral approach and a constant attention to unstabilized phenomena has to be promoted.